Effect of Speed and Surface Type on Individual Rein and Combined Left–Right Circle Movement Asymmetry in Horses on the Lunge - Pfau, Thilo; Persson-Sjodin, Emma; Gardner, Harriet; Orssten, Olivia; Hernlund, Elin; Rhodin, Marie (Frontiers in Veterinary Science, 2021)
Differences in movement asymmetry between surfaces and with increasing speed increase the complexity of incorporating gait analysis measurements from lungeing into clinical decision making. This observational study set out to quantify by means of quantitative gait analysis the influence of surface and speed on individual-rein movement asymmetry measurements and their averages across reins (average-rein measurements). Head, withers and pelvic movement asymmetry was quantified in 27 horses, identified previously as presenting with considerable movement asymmetries on the straight, during trot in-hand and on the lunge on two surfaces at two speeds. Mixed linear models (P<0.05) with horse as random factor, surface, speed category (and direction) as fixed factors analysed effects on 11 individual-rein and average-rein asymmetry measures. Limits of agreement quantified differences between individual-rein and average-rein measurements. A higher number of individual-rein asymmetry variables – particularly when the limb that contributed to movement asymmetry on the straight was on the inside of the circle – were affected by speed (nine variables, all P <=0.047) and surface (three variables, all P<=0.037) compared to average-rein asymmetry variables (two for speed, all P<=0.003; two for surface, all P<=0.046). Six variables were significantly different between straight-line and average-rein assessments (all P<=0.031) and asymmetry values were smaller for average-rein assessments. Limits of agreement bias varied between +0.4mm and +4.0mm with standard deviations between 3.2mm and 12.9mm. Fewer average-rein variables are affected by speed highlighting the benefit of comparing left and right rein measurements. Only one asymmetry variable showed a surface difference for individual-rein and average-rein data, emphasizing the benefit of assessing surface differences on each rein individually. Variability in straight-line versus average-rein measurements across horses and exercise conditions highlight the potential for average-rein measurements during the diagnostic process; further studies after diagnostic analgesia are needed.